End group reactions of RAFT-Prepared (Co)polymers - Harvison, M.; Roth, P.; Davis, T.; Lowe, Andrew (2011)
This review highlights the chemistry of thiocarbonylthio groups with an emphasis on chemistry conducted at ω or α and ω chain-ends in copolymers prepared by reversible addition–fragmentation chain-transfer (RAFT) radical polymerization. We begin by giving a general overview of reactions associated with the thiocarbonylthio groups, followed by examples associated with macromolecular thiols.